"Whare ye ennemy used to bury there dead": A New Englander burial at the 18th century Fortress of Louisbourg in Atlantic Canada. (11th October 2018) - Scott, Amy B.; Morgan, Jennifer A.; MacInnes, Sarah; Fonzo, Mattia; Hinton, Jessica
Abstract: Known as one of the largest and most expansive French fortress sites in North America, Louisbourg had a short yet rich history of prosperity, warfare, and abandonment during the 18th century. Throughout its tumultuous 45‐year history, the community at Louisbourg was a mosaic of individuals including civilians, soldiers, fishermen, merchants, and privateers, originating from both North America and Europe. This diverse population no doubt contributed to Louisbourg's large and multifaceted cemetery composition. During recent excavations at Louisbourg's Rochefort Point, variable burial patterns have begun to emerge that contribute to our understanding of who these individuals were and how they fit within this 18th century community. This paper presents a case study analysis of Burial 21/2017, an adult male aged between 27 and 33 years who was buried in a coffin that bore biographical information that is consistent with previously documented English burials. When comparing this unique coffin adornment with temporally similar examples from Britain and other British colonies, it is clear that despite burial on French soil, this individual's identity as a New Englander was maintained through mortuary treatment. Evidence of healed fracture trauma to multiple skeletal elements, infection, and likely gout speaks to their lived experience as a soldier. This case study highlights the significance of burial context when extrapolating elements of identity from skeletal remains and the challenges of bioarchaeological research when working in regions with highly transient and mobile individuals.